(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Digital vs. face to face in teaching the discipline Romanian Civilization and Culture at the Preparatory Year of Romanian Language for Foreign Citizens.The present study aimed to show that in the didactic activity of the Romanian Civilization and Culture discipline of the Preparatory Year of Romanian Language for Foreign Citizens, a strategy that combines modern and traditional methods, digital technique with direct encounters with certain people and situations, is effective. The teacher, who is the director of the teaching activities, must adapt his style according to the level of the group, but also to certain external factors (the COVID-19 period), so as to offer foreign students a real image of Romania, the city they are in, of Romanian traditions and customs, cultural and sports personalities, etc.